2018
DOI: 10.1002/jhbp.569
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive preservation versus splenectomy during distal pancreatectomy: a systematic review and meta‐analysis

Abstract: Based on this study, SPDP has significantly superior outcomes compared to DPS. When a spleen is preserved, SVP has better outcomes over WT for reducing splenic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 48 publications
(61 reference statements)
1
52
2
2
Order By: Relevance
“…There are many retrospective nonrandomized studies comparing the Warshaw operation, the Kimura technique (splenic vessels preservation), and splenectomy in distal pancreatectomy, 11,13,[45][46][47] but none has been performed about total pancreatectomy. To our knowledge, the present study represents the first observational study of surgical outcomes and survival comparing the Warshaw technique with conventional total pancreatectomy and splenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many retrospective nonrandomized studies comparing the Warshaw operation, the Kimura technique (splenic vessels preservation), and splenectomy in distal pancreatectomy, 11,13,[45][46][47] but none has been performed about total pancreatectomy. To our knowledge, the present study represents the first observational study of surgical outcomes and survival comparing the Warshaw technique with conventional total pancreatectomy and splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Nakao et al42 found that compared with pylorus-preserving and subtotal stomach-preserving total pancreatectomies, total pancreatectomy with distal gastrectomy could reduce postoperative gastric venous congestion and bleeding. Therefore, spleen-preserving total pancreatectomy using the Warshaw technique can be considered reasonable and perhaps preferable in selected patients with pancreatic cancers.There are many retrospective nonrandomized studies comparing the Warshaw operation, the Kimura technique (splenic vessels preservation), and splenectomy in distal pancreatectomy,11,13,[45][46][47] but none has been performed about total pancreatectomy. In contrast to the report by Ferrone et al,14 we observed two patients developed splenomegaly and subsequent thrombocytopenia, but neither of them had evidence of bleeding.…”
mentioning
confidence: 99%
“…First, we did not discriminate spleen‐vessel preserving LDP from standard LDP with splenectomy. Our systematic review of the literature demonstrated that spleen‐preserving LDP has significantly superior outcomes compared to LDP with splenectomy, and in a spleen‐preserving setting, vessel‐preservation has better outcomes over Warshaw operation (vessel‐resection) in terms of reducing splenic complications . However, many Japanese institutions prefer not to perform spleen‐preserving LDP because of the complexity of the procedure.…”
Section: Discussionmentioning
confidence: 96%
“…SPDP is beneficial for patients, because it can prevent an increased risk of overwhelming postsplenectomy infection by preserving the splenic immunological function [15]. Laparoscopic surgery is desirable not only because it is minimally invasive, but also because it favors spleen preservation due to a magnified laparoscopic view, which allows for safe dissection of the small pancreatic vessels [16].…”
Section: Discussionmentioning
confidence: 99%